Differential Regulation of CsrC and CsrB by CRP-cAMP in Salmonella enterica - El Mouali, Youssef; Esteva-Martínez, Guillem; García-Pedemonte, David; Balsalobre, Carlos (Frontiers in Microbiology, 2020)
Post-transcriptional regulation mediated by regulatory small RNAs (sRNAs) has risen as a key player in fine-tuning gene expression in response to environmental stimuli. Here, we show that, in Salmonella enterica, the central metabolic regulator CRP-cAMP differentially regulates the sRNAs CsrB and CsrC in a growth phase-dependent manner. While CsrB expression remains unchanged during growth, CsrC displays a growth phase-dependent expression profile, being weakly expressed at the logarithmic growth phase and induced upon entry into stationary phase. We show that CRP-cAMP contributes to the expression pattern of CsrC by repressing its expression during the logarithmic growth phase. The CRP-cAMP mediated repression of CsrC is independent of SirA, a known transcriptional CsrB/CsrC activator. We further show that the sRNA Spot 42, which is derepressed in a crp strain, upregulates CsrC during logarithmic growth. We propose a model where the growth-dependent regulation of CsrC is sustained by the CRP-cAMP-mediated repression of Spot 42. Together, our data point towards a differential regulation of the sRNAs CsrB and CsrC in response to environmental stimuli, leading to fine-tuning of gene expression via the sequestration of the RNA-binding protein CsrA.